6-5y=-4-6y

Simple and best practice solution for 6-5y=-4-6y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-5y=-4-6y equation:


Simplifying
6 + -5y = -4 + -6y

Solving
6 + -5y = -4 + -6y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '6y' to each side of the equation.
6 + -5y + 6y = -4 + -6y + 6y

Combine like terms: -5y + 6y = 1y
6 + 1y = -4 + -6y + 6y

Combine like terms: -6y + 6y = 0
6 + 1y = -4 + 0
6 + 1y = -4

Add '-6' to each side of the equation.
6 + -6 + 1y = -4 + -6

Combine like terms: 6 + -6 = 0
0 + 1y = -4 + -6
1y = -4 + -6

Combine like terms: -4 + -6 = -10
1y = -10

Divide each side by '1'.
y = -10

Simplifying
y = -10

See similar equations:

| 4x-2+3x= | | 46h=4h^3+5h^2 | | -7x-11y-5x+15y= | | -5x+18-3(x-1)=8x-(7x-9)+6x+6 | | V(x)=33x+162findx | | 12z+17=11z | | C=38.17+0.50 | | 2z^8/7z^7 | | v=144(3.14) | | 4(w-13)+17=19 | | -9x-5(3-4x)=6(x-4)-36 | | -7(x+4)= | | X=-(-10)/2(-5) | | 6h-h+2=17 | | 3x+7(x-9)=3(x-14) | | 6x+7=7x-1 | | Sin=-2 | | 14-w=17 | | cosz=-2 | | -1/2=3/5y-1/3 | | 9(3a+8)= | | cosz=-3 | | 4x^4/6/5x^3/6 | | -1/3v-1/2=-3/7 | | 12+2j=-j | | 5X=245 | | Y=-4x^2+16x-16 | | (4x+25)+x=180 | | 20+2k=-18k | | 5x+6=30+3x | | 5p^2+3=12p | | 3x^2+9x=-30 |

Equations solver categories